Analysis of Pension Schemes Disclosures of UK - FTSE 100 Companies 2005-2006 - Sun, Yulu (2007)
This study aims to examine the level and quality of disclosures with regard to pension obligations, with particular focus on principal actuarial assumptions among the FTSE 100 companies under IFRS and UK GAAP in 2005 and 2006. The increasing risks behind the pension liabilities have highlighted the need for more informative and accurate pension disclosures. Investors need more information on pensions in order to understand the underlying risks and adjust their investment decisions accordingly. A sample of 20 of the listed FTSE 100 companies, between 2005 and 2006, was taken to explore the quality of pension disclosures. This study makes original and unique contribution by comparing the sample disclosure scores with the benchmark, Generico, to enable the quality of disclosures to be explored. The study found that there is a general improvement in both the overall levels of pension disclosures and principal actuarial assumptions disclosures, but the quality of the disclosures is still poor in comparison with Generico. This result raises questions regarding pension deficits volatility and suggests that changes in life expectancy, volatility of inflation rates, discount rates and the equity markets are still the key factors for the pension risks. Adoption of IFRS improves the quality of pension disclosures in general. This study also looks for positive correlations between the amount of text units of pension information and disclosure scores. This study further discusses issues related to the uses of language in annual reports, overseas healthcare benefits etc. Finally, some recommendations, about future presentations of corporate pension information, improvement of accounting regulations and potential appealing directions of future research, are presented.